Harnessing Fruit and Vegetable Waste for Biofuel Production: Advances and Scope for Future Development - Ankita Sharma; Aman Jyoti; Aniket More; Mahendra Gunjal; Prasad Rasane; Mukul Kumar; Sawinder Kaur; Sezai Ercisli; Sushma Gurumayum; Jyoti Singh (eFood)
ABSTRACT Extreme exploitation of petroleum fuels has raised concerns around global warming due to increased greenhouse gas emissions, which by the year 2040 are expected to rise by around 43 billion metric tons. Biofuels have gained popularity in recent years because of their renewable and environmentally friendly prospects. Second‐generation biodiesel is generated from nonedible raw materials such as food waste, and is suggested to have lesser negative impacts on the environment and does not threaten food security. Edible fruit waste (7.65 kg/person) and edible vegetable waste (16 kg/person) is suggested to have highest contribution in the 38% of the global food waste. Annually, this corresponds to 15.78 m2 of cropland usage, 1.358 kg CO2 equivalent, 232.87 g of nitrogen usage, 3810.6 L of freshwater usage, and 38.544 g of phosphorus usage per person for agricultural production. FVW includes peels, seeds, crops, leaves, straw, stems, roots, or tubers. This waste can be utilized as feedstock for biofuel instead of burning, dumping, or landfilling, which leads to economic, environmental, and health issues such as water‐borne diseases, respiratory diseases, and lung diseases. Converting lignocellulosic mass into green energy including biogas, bioethanol, and biohydrogen can help in agricultural waste management while also contributing to carbon‐neutral model. Past studies have shown the potential of using fruit and vegetable waste in energy generation, jet fuels, and general diesel engines. This review focuses on the latest advances in biofuel production technology, with an emphasis on new pretreatments, production technologies, and recent works to improve biofuel production from lignocellulosic biomass.